USING MARKOV MODEL IN RELIABILITY ASSESSMENT OF AN ELECTRICAL POWER PLANT (Journal of Engineering, 2005)
The aim of this work is to make an evaluation to the reliability and availability of an electrical power plant as special kind of production systems to assess its ability in providing power with acceptable quality at a given period of time. Markov model was used as an analytical tool in assessment of the reliability and availability of a production power plant in Iraq, and especially for its four new steam-power units, which considered as basic power units of this plant This model (Markov) was used for the first once in assessment of power production system in Iraq. and prove its ability to provide a general evaluation for the performance of the power plant during a period of time Since the method has too extensișe mathematical operations. Matlab system (version 6.5) was used to formulize two computerized programs. once far define the mathemities model of the problem and the other for the analysis and plot the curves